Renaissance philosophy - Copenhaver, Brian P. 1942-; Schmitt, Charles B. (Oxford Univ. Pr., 1992)
The Renaissance has long been recognized as a brilliant moment in the development of Western civilization. However, little attention has been devoted to the distinct contributions of philosophy to Renaissance culture. This volume introduces the reader to the philosophy written, read, taught, and debated during the period traditionally credited with the 'revival of learning'. Beginning with original sources still largely inaccessible to most readers, and drawing on a wide range of secondary studies, the authors examine the relation of Renaissance philosophy to humanism and the universities, the impact of rediscovered ancient sources, the recovery of Plato and the Neoplatonists, and the evolving ascendancy of Aristotle. Renaissance Philosophy also explores the original contributions of major figures including Bruni, Valla, Ficino, Pico della Mirandola, Pomponazzi, Machiavelli, More, Vitoria, Montaigne, Bruno, and Campanella. In this work the rich insights and inheritance of Renaissance philosophy are made available to the student and the general reader. Renaissance Philosophy not only demonstrates the uses of ancient and medieval philosophy by Renaissance thinkers, but also throws light on the early origins of modern philosophy.
Keywords: Geschichte 1400-1600; Filosofie; Filosofía renacentista; Philosophie de la Renaissance; Renaissance; Philosophie; Philosophy, Renaissance; Geschichte